2022
DOI: 10.1111/aogs.14387
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive azithromycin prophylaxis protects women from uterine cesarean scar defect: A randomized controlled trial

Abstract: Introduction: Cesarean scar defect (CSD) is a long-term outcome of cesarean section (CS) and associated with numerous gynecological and obstetric problems. Previous studies indicate that infection may be a risk factor for CSD. Adjunctive azithromycin was shown to reduce the risk of postoperative infection in patients undergoing non-elective primary cesarean delivery in labor or after the rupture of membranes compared with standard antibiotic prophylaxis. This study investigated the protective effect of adjunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Ten publications, published between 2003 and 2022, from a total of 1023 connected investigations that met the inclusion criteria were chosen and involved in the investigation. [26][27][28][29][30][31][32][33][34][35] The results of these researches are presented in Table 2. A total of 22 676 females with CS were in the chosen investigations' starting point, 14 034 of them were…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ten publications, published between 2003 and 2022, from a total of 1023 connected investigations that met the inclusion criteria were chosen and involved in the investigation. [26][27][28][29][30][31][32][33][34][35] The results of these researches are presented in Table 2. A total of 22 676 females with CS were in the chosen investigations' starting point, 14 034 of them were…”
Section: Resultsmentioning
confidence: 99%
“…Ten publications, published between 2003 and 2022, from a total of 1023 connected investigations that met the inclusion criteria were chosen and involved in the investigation 26‐35 . The results of these researches are presented in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although some studies have demonstrated reduced CSD prevalence with decidual exclusion, others have indicated that judicious inclusion of the decidua may reduce CSD prevalence [53]. This observed benefit may result from a lower likelihood of inadvertent omission of the deep myometrial layers and a more physiologic reapproximation of the hysterotomy [41,57] Multidose perioperative antibiotics and adding a single dose of azithromycin to cephalosporin prophylaxis have been shown to reduce CSD prevalence [61,62].…”
Section: Preventionmentioning
confidence: 99%